Cdk9 and H2Bub1 signal to Clr6-CII/Rpd3S to suppress aberrant antisense transcription. Issue 13 (4th June 2020) - Sansó, Miriam; Parua, Pabitra K; Pinto, Daniel; Svensson, J Peter; Pagé, Viviane; Bitton, Danny A; MacKinnon, Sarah; Garcia, Patricia; Hidalgo, Elena; Bähler, Jürg; Tanny, Jason C; Fisher, Robert P
Abstract: Mono-ubiquitylation of histone H2B (H2Bub1) and phosphorylation of elongation factor Spt5 by cyclin-dependent kinase 9 (Cdk9) occur during transcription by RNA polymerase II (RNAPII), and are mutually dependent in fission yeast. It remained unclear whether Cdk9 and H2Bub1 cooperate to regulate the expression of individual genes. Here, we show that Cdk9 inhibition or H2Bub1 loss induces intragenic antisense transcription of ∼10% of fission yeast genes, with each perturbation affecting largely distinct subsets; ablation of both pathways de-represses antisense transcription of over half the genome. H2Bub1 and phospho-Spt5 have similar genome-wide distributions; both modifications are enriched, and directly proportional to each other, in coding regions, and decrease abruptly around the cleavage and polyadenylation signal (CPS). Cdk9-dependence of antisense suppression at specific genes correlates with high H2Bub1 occupancy, and with promoter-proximal RNAPII pausing. Genetic interactions link Cdk9, H2Bub1 and the histone deacetylase Clr6-CII, while combined Cdk9 inhibition and H2Bub1 loss impair Clr6-CII recruitment to chromatin and lead to decreased occupancy and increased acetylation of histones within gene coding regions. These results uncover novel interactions between co-transcriptional histone modification pathways, which link regulation of RNAPII transcription elongation to suppression of aberrant initiation.